Inhibition of autophagosome-lysosome fusion by ginsenoside Ro via the ESR2-NCF1-ROS pathway sensitizes esophageal cancer cells to 5-fluorouracil-induced cell death via the CHEK1-mediated DNA damage checkpoint. Issue 9 (1st September 2016) - Zheng, Kai; Li, Yan; Wang, Shaoxiang; Wang, Xiao; Liao, Chenghui; Hu, Xiaopeng; Fan, Long; Kang, Qiangrong; Zeng, Yong; Wu, Xuli; Wu, Haiqiang; Zhang, Jian; et al.
ABSTRACT: Modulation of autophagy has been increasingly regarded as a promising cancer therapeutic approach. In this study, we screened several ginsenosides extracted from Panax ginseng and identified ginsenoside Ro (Ro) as a novel autophagy inhibitor. Ro blocked the autophagosome-lysosome fusion process by raising lysosomal pH and attenuating lysosomal cathepsin activity, resulting in the accumulation of the autophagosome marker MAP1LC3B/LC3B and SQSTM1/p62 (sequestosome 1) in various esophageal cancer cell lines. More detailed studies demonstrated that Ro activated ESR2 (estrogen receptor 2), which led to the activation of NCF1/p47 PHOX (neutrophil cytosolic factor 1), a subunit of NADPH oxidase, and subsequent reactive oxygen species (ROS) production. Treatment with siRNAs or inhibitors of the ESR2-NCF1-ROS axis, such as N-acetyl-L -cysteine (NAC), diphenyleneiodonium chloride (DPI), apocynin (ACN), Tiron, and Fulvestrant apparently decreased Ro-induced LC3B-II, GFP-LC3B puncta, and SQSTM1, indicating that ROS instigates autophagic flux inhibition triggered by Ro. More importantly, suppression of autophagy by Ro sensitized 5-fluorouracil (5-Fu)-induced cell death in chemoresistant esophageal cancer cells. 5-Fu induced prosurvival autophagy, and by inhibiting such autophagy, siRNAs against BECN1/beclin 1, ATG5, ATG7, and LC3B enhanced 5-Fu-induced autophagy-associated and apoptosis-independent cell death. We observed that Ro potentiates 5-Fu cytotoxicity via delaying CHEK1 (checkpoint kinase 1) degradation and downregulating DNA replication process, resulting in the delayed DNA repair and the accumulation of DNA damage. In summary, these data suggest that Ro is a novel autophagy inhibitor and could function as a potent anticancer agent in combination therapy to overcome chemoresistance.